Implants for surgery - hydroxyapatite - part 3: chemical analysis and characterization of crystallinity and phase purity (ISO 13779-3:2008, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Mohd Yusof, Hyzan; et al. (SIRIM, 2010)
ISO 13779-3:2008 specifies methods of test for the chemical analysis and assessment of crystallinity and phase composition of hydroxyapatite-based materials such as coatings and sintered products.